Teacher's Perception of the Online Learning Process at SD Inpres Tinggimae, Gowa Regency - Zarah Fratiwi Nur; Suardi Suardi; Kaharuddin Kaharuddin (Universitas of Muhammadiyah Makassar, 2022)
The main problems in this study are the teacher's perception of the online learning process at SD Inpres Tinggimae, problems faced by teachers during the online learning process at SD Inpres Tinggimae, and solutions to problems faced by teachers at SD Inpres Tinggimae. The type of research used in this study is a qualitative research using the mixed method concurrent embedded method. Data collection techniques carried out include: Observation, interviews, documents, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) online learning is not going well because it has many obstacles and is also ineffective. Problems or obstacles faced by teachers during the online learning process are the absence of supporting facilities such as mobile phones, quotas, and internet networks. The solution to the problem is that students come to school to take assignments or learning materials, study with teachers, seek good network access, also use appropriate learning methods and create discussion forums for parents and teachers. Based on the results of this study, it can be concluded that online learning is not suitable for use at the elementary school level because basically the learning of elementary school children is still teacher-centered. Online learning makes learning objectives not achieved. In addition, there are many obstacles so that learning does not run well and is also effective.